2022
DOI: 10.21037/atm-22-1891
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analyses of the role of m6A RNA methylation regulators in abdominal aortic aneurysm

Abstract: Background: N6-methyladenosine (m6A) is found in almost all nuclear RNAs of eukaryotes, playing an important and diverse role in many biological processes. Nonetheless, the roles of m6A regulators in abdominal aortic aneurysm (AAA) unknown. Therefore, there is a pressing need to identify m6A RNA methylation regulators in the diagnosis of AAA, determination of individualized risk, discovery of therapeutic targets, and improve understanding of pathogenesis.Methods: The GSE98278 dataset were obtained from the Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Thereafter, we focused on exploring the exact downstream mechanism of RBM15 in CRC cell functions. Accumulating studies have confirmed that RBM15‐catalyzed m 6 A modification participates in tumor pathogenesis and progression by regulating target gene expression and stability 29,31 . KLFs are a group of transcriptional regulators implicated in the development of certain malignancies, and some members of the KLF family are promising prognostic indicators for CRC 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, we focused on exploring the exact downstream mechanism of RBM15 in CRC cell functions. Accumulating studies have confirmed that RBM15‐catalyzed m 6 A modification participates in tumor pathogenesis and progression by regulating target gene expression and stability 29,31 . KLFs are a group of transcriptional regulators implicated in the development of certain malignancies, and some members of the KLF family are promising prognostic indicators for CRC 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown the expression pattern and functional significance of m6A-related genes in AAA (Zhang et al, 2021). m6A-related genes were found to play non-negligible roles in the occurrence of AAA ruptured (rAAA) (Fu et al, 2022). Besides, increased methylation levels of YTHDF3, FTO, and METTL14 were revealed to be associated with the progression of AAA (He et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…NSUN2 influences autotaxin expression and T cell recruitment to control aneurysm development (Miao et al, 2021). In AAA, Frontiers in Genetics frontiersin.org RBM15 knockdown decreased CASP3 expression in an m6Adependent way (Fu et al, 2022). In AAA, YBX1 was discovered to be a direct target of GAS5, and it also collaborated with GAS5 to control the downstream target p21 through a positive feedback loop (He et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…The HNRNPA2B1, RBMX, and RBM15 levels were also observed to be significantly elevated in the PASMCs of IPAH patients ( Figure 8B ). RBM15 knockdown decreased the expression of CASP3 in an m6A-dependent manner and inhibited human aortic SMCs apoptosis ( Fu et al, 2022 ). RBM15 and RBMX facilitate the proliferation and invasiveness of tumors, such as hepatocellular carcinoma ( Song et al, 2020 ; Cai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%